Antibacterial activity of amine-functionalized silver-loaded natural zeolite clinoptilolite / Nik Ahmad Nizam Nik Malek and Siti Aishah Mohd Hanim - Nik Malek, Nik Ahmad Nizam; Mohd Hanim, Siti Aishah (Faculty of Applied Sciences, 2021)
The antibacterial activity of amine-functionalized silver-loaded natural zeolite clinoptilolite was analysed against Gram-negative Escherichia coli ATCC 11229 and a comparison was made with raw clinoptilolite, silver-loaded clinoptilolite, and amine-functionalized clinoptilolite with APTES (3-Aminopropyl) triethoxysilane. Results from the characterization of the samples using Fourier transform infrared (FTIR) spectroscopy showed that the silver-loaded clinoptilolite was functionalized with APTES without affecting the original framework structure of the clinoptilolite. The antibacterial activity of the analysed samples based on disc diffusion technique (DDT) and minimum inhibition concentration (MIC) showed that the silver-loaded clinoptilolite (150 % of cation exchange capacity of clinoptilolite) had the highest antibacterial activity, as compared to amine-functionalized silver-loaded zeolite. This study showed that the functionalization of silverloaded clinoptilolite could affect the release and action of silver ions to kill or inhibit bacterial growth. However, it showed that the natural zeolite clinoptilolite could become a good carrier system for the antibacterial metal ion, especially silver ions.